Academic advising assessment practices: a descriptive study - Powers, Keith L. (Kansas State University, 2012)
In academic courses, assessment is used to evaluate the effect of teaching on student learning. Academic advising has been viewed as a form of teaching (Crookston, 1972); therefore, it is necessary to assess the effect of academic advising on student learning. The best practices of assessment of academic achievement involve three key steps: the identification of student learning outcomes (i.e., what is assessed), the development and use of good measures of student learning (i.e., how assessment is conducted), and the use of sound professional judgment to understand the information gathered and to make changes to improve student learning (i.e., how assessment results are used). However, the assessment of academic advising is often minimal, narrow, and inconsistent. Further, when assessment of academic advising is conducted, it is most commonly a survey of student satisfaction of their advising experience (Carlstrom, 2012; Habley, 2004; Macaruso, 2007; Robbins, 2009). The purpose of this study was to learn about the assessment practices in the profession by surveying those who conducted or were responsible for assessment of academic advising. The study found that 80% of participants had identified academic advising student learning outcomes in their situation. The most frequently reported outcome was that students would know degree requirements. A little over half of the participants who identified student learning outcomes assessed the achievement of those outcomes and student surveys were the most frequently reported measure used. Seven percent of participants reported to use three or more measures to assess student learning outcomes. Multiple measures are needed in assessing outcomes to gather comprehensive evidence of outcomes achievement. Sixty percent of participants reported they used assessment information to make decisions regarding improvement of services and student learning. The most frequently reported use of information was making revisions to the advising process/delivery outcomes. The results of the survey indicated that participants viewed advisors’ belief in assessment as important to facilitating assessment of academic advising. They also viewed administrators’ use of information in making decisions and changes to improve advising practices and increase student learning as important.
Keywords: Academic advising; Assessment; Student learning outcomes; Higher Education (0745); Higher Education Administration (0446)